Penggunaan Hak Preogatif Presiden dalam Pengangkatan Menteri di Sistem Pemerintahan RI (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The prerogative is a privilege that belongs to the President which cannot be contested by other state institutions that use a presidential government system, namely the president is the head of state as well as the head of government in Indonesia. In the prerogative there is nothing specific to oversee a prerogative, but one of the supervision of this privilege is supervision in the cabinet ministers who are assistants to the president.The problems studied are 1) What is the meaning of the President's prerogative in the Indonesian government system. 2) How to Use the President's Prerogative in Appointing Ministers in the Indonesian Government System 3). What are the Forms of Supervision of Prerogatives in Cabinet Ministers? This study aims to identify and explain the meaning of presidential prerogatives, the system of government used in the application of prerogatives and oversight of privileges used in Indonesia. This research uses research methods through library research and normative research with reference to relevant laws and regulations and other legal materials related to substance in research and application regarding reading, listening, understanding, and reviewing the application of laws, scientific work. , books and literature related to the problem under study. In the meaning of prerogative is a privilege of a head of state in carrying out state duties.